2011
DOI: 10.1017/s0003598x00068368
|View full text |Cite
|
Sign up to set email alerts
|

Aging cremated infants: the problem of sacrifice at the Tophet of Carthage

Abstract: The Greeks and Romans reproached the Phoenicians for the sacrifice of infants, and the excavation of cremated infants at 'Tophets' (named after the sacrificial site in Jerusalem mentioned in the Bible) seems to bear this out. However, the argument for infant sacrifice depends largely on a skewed age profile, and age is not easy to determine. The authors approach this problem with a battery of new techniques, showing that in the Tophet of Carthage the majority of the infants died between one and one and a half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 19 publications
0
42
0
1
Order By: Relevance
“…We identified 1422 deciduous teeth, 74 permanent teeth and 350 petrous bones, as well as smaller numbers of other skeletal elements representing a minimum number of 372 individuals (Supplementary Tables S1 & S2; Smith et al 2011). All showed evidence of incineration with colour change indicative of temperatures between 200 • C (yellowishbrown) to 700 • C (whitish-grey) (Bonucci & Graziani 1975;Shipman et al 1984).…”
Section: Scattergram Showing Length-breadth Measurements Of the Crementioning
confidence: 99%
See 3 more Smart Citations
“…We identified 1422 deciduous teeth, 74 permanent teeth and 350 petrous bones, as well as smaller numbers of other skeletal elements representing a minimum number of 372 individuals (Supplementary Tables S1 & S2; Smith et al 2011). All showed evidence of incineration with colour change indicative of temperatures between 200 • C (yellowishbrown) to 700 • C (whitish-grey) (Bonucci & Graziani 1975;Shipman et al 1984).…”
Section: Scattergram Showing Length-breadth Measurements Of the Crementioning
confidence: 99%
“…Measurements taken on computerised 3D models compiled from serial micro-CT scans showed that maximum circumference in the Tophet developing molars was 18 per cent smaller than that of non-cremated teeth of similar crown height (Smith et al 2011). To evaluate the effect of such shrinkage on age estimations, we compared crown height measurements reported by Soleil et al (1958) for incinerated teeth with those of non-cremated forensic specimens of the same gestational age (Tables 1 & 2).…”
Section: Scattergram Showing Length-breadth Measurements Of the Crementioning
confidence: 99%
See 2 more Smart Citations
“…This marker is routinely used in forensic investigations (e.g., Gustafson 1966;Skinner and Dupras 1993;Stavrianos et al 2010;Whittaker and Richards 1978) and its presence/absence, position and variation patterns are also increasingly considered in studies on population samples from archaeological sites (e.g., Alexandersen et al 1998;Antoine et al 2009;Bondioli and Macchiarelli 1999;FitzGerald and Saunders 2005;FitzGerald et al 1999FitzGerald et al , 2006Macchiarelli and Bondioli 2000;Macchiarelli et al 2006a;Rossi et al 1997Rossi et al , 1999Schwartz et al 2010;Smith and Avishai 2005;Smith et al 2011). However, likely because of methodological constraints related to the only recent availability of noninvasive highresolution investigative methods in paleobiology (e.g., Macchiarelli et al 2004Macchiarelli et al , 2008Mazurier et al 2006;Tafforeau 2004;Tafforeau et al 2006;Smith and Tafforeau 2008), its use in the study of the human fossil record is still very limited (e.g., Macchiarelli et al 2006b;Smith and Tafforeau 2008;Smith et al 2010a;Tafforeau and Smith 2008;Zanolli et al 2011).…”
mentioning
confidence: 99%